Perbaikan Efektivitas Bank Indonesia Sistem Manajemen Aset (BISMA) dengan Perancangan Standar Operasional Prosedur (SOP) - Permatasari, Carina Intan (Metris: Jurnal Sains dan Teknologi, 2017)
Concerning with the enactment of the Regulation of the Governor of Bank Indonesia Number 11/2/PDG/ 2009 dated February 20, 2009 on the Management of Logistics of Bank Indonesia, particularly regarding the management of Bank Indonesia's goods, it is necessary to assume the Asset Management System of Bank Indonesia, called BISMA. BISMA is a Bank Indonesia Asset Management application that consists of interrelated modules for recording asset data, asset recognition, asset depreciation, asset optimization, and asset resolution development using information technology. Although the application of this application runs well but the purpose of this paper is to see its effectiveness by analyzing the application of BISMA both in terms of field conditions or literature studies and make improvements with SOP design. Where the performance of the SOP is raced on the Government Regulation of the Republic of Indonesia No. 6 of 2006, PMK RI No. 96 / PMK.06 / 2007, PMK RI No. 102 of 2009 and Regulation of the Director General of KN No 07 / KN / 2009.